Accuracy of CT Angiography for Differentiating Pseudo-Occlusion from True Occlusion or High-Grade Stenosis of the Extracranial ICA in Acute Ischemic Stroke: A Retrospective MR CLEAN Substudy - Kappelhof, M.; Marquering, H.A.; Berkhemer, O.A.; Borst, J.; van der Lugt, A.; van Zwam, W.H.; Vos, J.A.; Lycklama à Nijeholt, G.; Majoie, C.B.L.M.; Emmer, B.J. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: The absence of opacification on CTA in the extracranial ICA in acute ischemic stroke may be caused by atherosclerotic occlusion, dissection, or pseudo-occlusion. The latter is explained by sluggish or stagnant flow in a patent artery caused by a distal intracranial occlusion. This study aimed to explore the accuracy of CTA for differentiating pseudo-occlusion from true occlusion of the extracranial ICA.MATERIALS AND METHODS: All patients from the Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands (MR CLEAN) with an apparent ICA occlusion on CTA and available DSA images were included. Two independent observers classified CTA images as atherosclerotic cause (occlusion/high-grade stenosis), dissection, or suspected pseudo-occlusion. Pseudo-occlusion was suspected if CTA showed a gradual contrast decline located above the level of the carotid bulb, especially in the presence of an occluded intracranial ICA bifurcation (T-occlusion). DSA images, classified into the same 3 categories, were used as the criterion standard.RESULTS: In 108 of 476 patients (23%), CTA showed an apparent extracranial carotid occlusion. DSA was available in 46 of these, showing an atherosclerotic cause in 13 (28%), dissection in 16 (35%), and pseudo-occlusion in 17 (37%). The sensitivity for detecting pseudo-occlusion on CTA was 82% (95% CI, 57–96) for both observers; specificity was 76% (95% CI, 56–90) and 86% (95% CI, 68–96) for observers 1 and 2, respectively. The κ value for interobserver agreement was .77, indicating substantial agreement. T-occlusions were more frequent in pseudo- than true occlusions (82% versus 21%, P < .001).CONCLUSIONS: On CTA, extracranial ICA pseudo-occlusions can be differentiated from true carotid occlusions.EVTendovascular treatmentMR CLEANMulticenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the NetherlandsT-occlusionoccluded intracranial ICA bifurcation